2013
DOI: 10.1007/s10162-013-0377-0
|View full text |Cite
|
Sign up to set email alerts
|

The Polarity Sensitivity of the Electrically Stimulated Human Auditory Nerve Measured at the Level of the Brainstem

Abstract: Recent behavioral studies have suggested that the human auditory nerve of cochlear implant (CI) users is mainly excited by the positive (anodic) polarity. Those findings were only obtained using asymmetric pseudomonophasic (PS) pulses where the effect of one phase was measured in the presence of a counteracting phase of opposite polarity, longer duration, and lower amplitude than the former phase. It was assumed that only the short high-amplitude phase was responsible for the excitation. Similarly, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 88 publications
8
64
1
Order By: Relevance
“…However, caution is required as anodic first stimulation was applied only twice per subject. A difference in tinnitus suppression between cathodic and anodic first charge-balanced electrical stimulation was initially expected as prior studies showed that anodic stimulation could be more sensitive than cathodic stimulation [Undurraga et al, 2010[Undurraga et al, , 2013Carlyon et al, 2013]. The cathodic phase is thought to stimulate the peripheral process while the anodic phase probably excites the nerve fibers more centrally [Rattay et al, 2001].…”
Section: Effect Of Polaritymentioning
confidence: 99%
“…However, caution is required as anodic first stimulation was applied only twice per subject. A difference in tinnitus suppression between cathodic and anodic first charge-balanced electrical stimulation was initially expected as prior studies showed that anodic stimulation could be more sensitive than cathodic stimulation [Undurraga et al, 2010[Undurraga et al, , 2013Carlyon et al, 2013]. The cathodic phase is thought to stimulate the peripheral process while the anodic phase probably excites the nerve fibers more centrally [Rattay et al, 2001].…”
Section: Effect Of Polaritymentioning
confidence: 99%
“…However, alternating polarity is not an option for some investigations, for instance, at the most peripheral stages the response is polarity dependent [10]. If the desired eABR investigation requires a specific polarity, other means of artifact reduction are required.…”
Section: Stimulimentioning
confidence: 99%
“…Alternating polarity stimulation was introduced in previous publications [7][8][9][10][11] for electric artifact suppression, especially for the rejection of post pulse artifact. However, alternating polarity is not an option for some investigations, for instance, at the most peripheral stages the response is polarity dependent [10].…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations